Potential Contribution of Antioxidant Mechanism in the Defensive Effect of Lycopene Against Partial Sciatic Nerve Ligation Induced Behavioral, Biochemical and Histopathological Modification in Wistar Rats - Goel, R.; Tyagi, N. (Drug Research, 2016)
Neuropathic pain is a severe and unbearable condition which arises due to activation of peripheral nociceptors after tissue damage, neuropathic pain is caused from anomalous physiology of central or peripheral nervous system and it may not be related to the ongoing tissue damage or inflammation. Involvement of oxidative damage has been reported in the pathophysiology of neuropathic pain. The purpose of this study was to examine the effect of lycopene to quench the free radicals produced as a result of the increased oxidative stress in neuropathic pain. Neuropathic pain was induced in wistar rats by partial sciatic nerve ligation. The effect was evaluated by assessing various behavioral parameters (thermal hyperalgesia, cold hyperalgesia), biochemical parameters (lipid peroxidation, reduced glutathione, superoxide dismutase and catalase) as well as histopathological parameters in sciatic nerve. During the experiment group of 8 rats each was administered drugs once daily intraperitonealy (I.P.) and naïve groups, sham group and sciatic nerve ligated group were treated with vehicle for the duration of 14 days. Partial sciatic nerve ligation (PSNL) significantly caused thermal hyperalgesia, cold hyperalgesia and oxidative damage compared to normal and sham groups. Daily administration of lycopene (25 mg/kg, 50 mg/kg) and gabapentin (100 mg/kg) considerably reversed hyperalgesia, cold hyperalgesia and attenuated oxidative stress when compared to control group. There was significant histological improvement in the in the architecture of myelinated and unmyelinated fibers. The results indicated that free radical generation mechanism might be involved in PSNL induced behavior, biochemical and histopathological changes in wistar rats.
Keywords: lycopene; gabapentin; catalase; hyperalgesia; histopathological